The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1021/cg7010259
|View full text |Cite
|
Sign up to set email alerts
|

Cu(SO3)47-: A Readily Accessible Building Block for New Coordination Polymers

Abstract: The combination of Cu(II) with excess sodium sulfite or a mixture of sodium sulfite and sodium hydrogensulfite produces a colorless solution consistent with the reduction of Cu(II) to Cu(I). The addition of divalent metal ions such as Mn 2+ , Co 2+ , Ni 2+ and Zn 2+ to such solutions, leads to the generation of coordination networks in which the divalent metal ions link together anions of formula Cu(SO 3 ) 4 7-. This symmetrical anion consists of a tetrahedrally coordinated Cu(I) center bound to the sulfur ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…When Mn 2+ is in excess, the pale pink crystals that separate have composition Na (H 2 O) 6 {[Cu I (SO 3 ) 4 ][Mn II (H 2 O) 2 ] 3 } and the topology of the coordination network is related to that of a simple cubic (α-Po) net. 5 However when copper is in excess the crystals obtained are 6 for an applied DC field of 1 T, gives a value of 0.505 cm 3 K mol −1 at 270 K (μ eff = 2.01 μ B ) and this slowly increases down to ∼50 K before a more rapid increase occurs, to reach 1.18 cm 3 K mol −1 at 3 K (μ eff = 3.07 μ B ) followed by a sharp decrease below 3 K reaching 1.06 cm 3 K mol −1 at 2 K. These data are indicative of intra-chain ferromagnetic coupling and the Curie-Weiss (χ M = C/(T − θ) linear dependence of χ M vs. 1/T confirms this with C = 0.53 cm 3 K mol −1 and θ = +3.2 K. A good fit of the data at temperatures above the maximum was obtained using a Fisher chain model 8 with g = 2.33(1) and J = 2.96(1) cm −1 . The sharp maximum at ∼3 K is possibly due to inter-chain antiferromagnetic coupling or to Zeeman effects involving the S = 1 ground state.…”
Section: Synthetic and Structural Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When Mn 2+ is in excess, the pale pink crystals that separate have composition Na (H 2 O) 6 {[Cu I (SO 3 ) 4 ][Mn II (H 2 O) 2 ] 3 } and the topology of the coordination network is related to that of a simple cubic (α-Po) net. 5 However when copper is in excess the crystals obtained are 6 for an applied DC field of 1 T, gives a value of 0.505 cm 3 K mol −1 at 270 K (μ eff = 2.01 μ B ) and this slowly increases down to ∼50 K before a more rapid increase occurs, to reach 1.18 cm 3 K mol −1 at 3 K (μ eff = 3.07 μ B ) followed by a sharp decrease below 3 K reaching 1.06 cm 3 K mol −1 at 2 K. These data are indicative of intra-chain ferromagnetic coupling and the Curie-Weiss (χ M = C/(T − θ) linear dependence of χ M vs. 1/T confirms this with C = 0.53 cm 3 K mol −1 and θ = +3.2 K. A good fit of the data at temperatures above the maximum was obtained using a Fisher chain model 8 with g = 2.33(1) and J = 2.96(1) cm −1 . The sharp maximum at ∼3 K is possibly due to inter-chain antiferromagnetic coupling or to Zeeman effects involving the S = 1 ground state.…”
Section: Synthetic and Structural Studiesmentioning
confidence: 99%
“…Mn 2+ , Co 2+ , Ni 2+ and Zn 2+ ). 5 The [Cu I (SO 3 ) 4 ] 7− component of these polymers consists of a Cu(I) centre surrounded tetrahedrally by the sulfur donors of four sulfite units. The highly charged [Cu I (SO 3 ) 4 ] 7− anion binds metal cations strongly, offering in principle numerous conceivable chelating modes, two very symmetrical possibilities being shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Robson and co‐workers41 reported the synthesis of the 1D Na 3 {[Cu I (SO 3 ) 4 ][Zn II (H 2 O) 2 ] 2 } · H 2 O and Na 3 {[Cu I (SO 3 ) 4 ][Co II (H 2 O) 2 ] 2 } · H 2 O, and 2‐D [Na 4 (H 2 O) 17 ][Ni(H 2 O) 6 ] 2 {[Cu(SO 3 ) 4 ] 2– [Ni(H 2 O) 2 ] 3 } and [Na 4 (H 2 O) 17 ][Co(H 2 O) 6 ] 2 {[Cu(SO 3 ) 4 ] 2 [Co(H 2 O) 2 ] 3 } coordination polymers, demonstrating for the first time the efficacy of the [Cu(SO 3 ) 4 ] 7– anion as a building block for the construction of novel polymeric architectures. Moreover, the same group reported recently42 a family of mixed‐valence Cu I/II /SO 3 2– coordination polymers based on the highly charged [Cu(SO 3 ) 4 ] 7– anion; the authors demonstrated the reactivity of the nucleophilic [Cu(SO 3 ) 4 ] 7– moiety towards first‐row transition metals resulting in finite {[Cu II (H 2 O)(bipy)] 4 [Cu I (SO 3 ) 4 ]}NO 3 · H 2 O, Na 12 {[Cu I (SO 3 ) 4 ] 2 Mn II } · 8H 2 O and Na 3 (H 2 O) 6 [Fe II (H 2 O) 6 ] 2 {[Cu I (SO 3 ) 4 ] 2 [Fe III (H 2 O)] 3 O} · H 2 O, and infinite Na 5 {[Cu II (H 2 O)][Cu I (SO 3 ) 4 ]} · 6H 2 O and (H 2 O) 6 {[Cu I (SO 3 ) 4 ][Mn II (H 2 O) 2 ] 3 } architectures.…”
Section: Novel Archetypesmentioning
confidence: 98%
“…In the sulfite group, the S atom is in a +4 intermediate oxidation state, which causes the sulfite anion to be readily oxidized to the sulfate ion and to appear unstable under hydrothermal and acidic conditions. For the purpose of synthesizing sulfitecontaining materials, the main strategy nowadays is to introduce soft acids, for example, Cu I , into the reactant system to stabilize the S IV moieties through coordination from the soft base site (S atom) of the sulfite group to the soft acid (Li et al, 2007(Li et al, , 2009Li & Mao, 2008Abrahams et al, 2008). There are very few examples of metal sulfites synthesized without the assistance of soft acids (Rao & Rao, 2007).…”
Section: Commentmentioning
confidence: 99%